Potential for Increasing Agricultural Water Productivity - Quandzie, Stephen (CGIAR Challenge Program on Water and Food, 2012)
Key  findings: The  research  revealed  the  following  key  things  about  agriculture  and  agricultural  water;  that   dry   season   gardening   is   considered   by   the   indigenes   as   one   of   the   means   by   which   poverty   and  transitional  (seasonal)  hunger  can  be  reduced. Those   agriculture   water   management   (AWM)   interventions   that   allow   individual   farmers   to   irrigate   independently   throughout   the   season   (dry)   produced   crop   water   consumption   factor  that  was  close  to  the  optimum  value  of  zero. For   those   agriculture   water   management   (AWM)   interventions   considered   within   the   study   area   potential   to   increase   agricultural   water   productivity   exist,   with   the   highest   existing   in   gravitational  flow  based  water  interventions. The   physical   crop   water   productivity   (PCWP),   economic   water   productivity   (EWP),   and   agriculture   land   productivity   (ALP)   were   generally   low   as   compared   to   FAO   values   for   sub-‐   saharan  areas  having  similar  biophysical  characters.